Complementary and Alternative Medicine Use Was Associated with Higher Perceived Physical and Mental Functioning in Early Systemic Sclerosis - Hunnicutt, Sonya E. (2008)
OBJECTIVE: This study assessed the use of complementary and alternative medicine (CAM) therapies in patients with early systemic sclerosis (scleroderma, SSc). METHODS: At the annual visit, SSc patients enrolled in the Genetics versus Environment in Scleroderma Outcomes Study (GENISOS) were queried about their use of CAM therapies and intended symptom target, including herbal or nutriceutical therapy, acupuncture, transcutaneous electrical neural stimulation (TENS) and mind-body therapy (relaxation, meditative, imagery). The CAM user SSc patients were compared to matched non-CAM users over two years for database results of demographic, clinical and health-related quality of life SF-36 questionnaires by analysis of covariance. RESULTS: 25% of the university GENISOS group were CAM users: age: 54 years; female: 89%; diffuse cutaneous involvement: 47%; total skin score: 13.5; Medsger severity index: 5.8. Over 70% used ≥1 CAM therapies for over 1 year, independent of health insurance. Symptoms targeted included arthritis/arthralgia, pain, GI dysmotility and fatigue. CAM users had significantly higher mean mental component summary (MCS) scores on SF-36 at Baseline and Year 2, (49 and 49.9), compared to non-CAM users (42 and 40.2, respectively, p<0.01). At Year 2, the CAM user group had significantly higher scores of SF-36 domains physical component score, role-physical, bodily pain and vitality, whereas scores declined in the non-CAM user group. CONCLUSION: In SSc, 70% of those in the CAM user group reported a long-term commitment to CAM therapies. Higher perceived mental functioning in CAM users might reflect more self-motivation to manage symptoms and subsequently, promote practices that result in higher perceived physical functioning.